MCM-41-supported platinum carbonyl cluster-derived asymmetric hydrogenation catalyst - Basu, Susmit; Paul, Himadri; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2005)
Anionic platinum carbonyl cluster has been ion paired with cinchonidium groups that are chemically bound to the surface of MCM-41 and fumed silica. In the hydrogenation of methyl pyruvate or acetophenone the fumed silica-based catalyst gives zero enantioselectivity, but under optimum conditions enantiomeric excesses of >90 and similar to40%, respectively, are obtained with the MCM-41-based catalyst. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: asymmetric catalysis; functionalized inorganic oxides; hydrogenation catalysts; platinum carbonyl cluster

MCM-41-supported platinum carbonyl cluster-derived catalysts for asymmetric and nonasymmetric hydrogenation reactions - Basu, Susmit; Mapa, Maitri; Gopinath, Chinnakonda S.; Doble, Mukesh; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2006)
Anionic platinum carbonyl Cluster ([Pt-12(CO)(24)](2-)) was ion-paired with the 3-chloropropyltrimethoxysilyl-ammonium group chemically bound to the surface of MCM-41. The materials undergo quick decarbonylation and have been characterized before decarbonylation by IR and UV-vis spectroscopy and after decarbonylation by XPS and TEM. They have been used as catalysts for the hydrogenations of methyl pyruvate, acetophenone, nitrobenzene, benzonitrile, and ethylacetoacetate. The support and the quaternary ammonium groups have significant effects on surface platinum concentration, crystallite size, and observed activity. In the hydrogenation of the prochiral substrates methyl pyruvate or acetophenone, the cinchonidine-based catalyst gives significant enantioselectivity under optimum conditions. A kinetic model that includes an enantioselective product-formation step and a hydrogen pressure-dependent step for the deactivation of the enantioselective sites gives reasonable agreement between predicted and observed enantioselectivity. The model is also in accordance with the XPS and TEM data. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: asymmetric/non-asymmetric catalysis; Enantioselectivity; functionalized MCM-41; hydrogenation catalysts; platinum carbonyl cluster

MCM-41-supported organometallic-derived nanopalladium as a selective hydrogenation catalyst - Maity, Niladri; Rajamohanan, Pattuparambil R.; Ganapathy, Subramanian; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Physical Chemistry C, 2008)
Palladium nanocatalysts have been prepared by anchoring (eta(3)-C(3)H(5))(2)Pd(2)Cl(2) onto dian-tine-functionalized MCM-41 supports followed by reaction with hydrogen under catalytic conditions. The catalyst precursor and used catalyst have been studied by solid-state NMR ((13)C, (29)Si), XPS, and TEM. The organometallic-derived catalyst exhibits the best performance (activity and selectivity) to date toward the selective hydrogenation of industrially relevant o- and m-chloronitrobenzene to the corresponding chloroaniline derivatives and is distinctly superior to 5% Pd/C. Grazing angle XPS studies reveal that conversion of the tethered molecular species to the nanoparticles of palladium produces a core-shell nanostructure.

MCM-41-supported ruthenium carbonyl cluster-derived catalysts for asymmetric hydrogenation reactions - Indra, Arindam; Basu, Susmit; Kulkarni, Dhanashree G.; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Applied Catalysis A-General, 2008)
{The anionic ruthenium carbonyl cluster [Ru-4(mu-H)(3)(CO)(12)](-) has been ion-paired with (3-chloropropyl)-trimethoxysilyl-cinchonidium or sparteinium groups chemically bound to the surfaces of MCM-41 [(MCM-41-)(-O)(3)SiCH2CH2CH2NR3+Cl-
Keywords: asymmetric catalysis; functionalized MCM-41; hydrogenation catalysts; nanocatalyst; ruthenium carbonyl cluster

MgCl2 center dot 4(CH3)(2)CHOH: a new molecular adduct and super active polymerization catalyst support - Thushara, K. S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2009)
A new molecular adduct, MgCl(2 center dot)4(CH3)(2)CHOH, has been synthesized and characterized for structural aspects and demonstrated for super active ethylene polymerization activity with TiCl4 to ultrahigh molecular weight polyethylene in high yield.

MgCl2 center dot 6PhCH(2)OH - a new molecular adduct as support material for ziegler-natta catalyst: synthesis, characterization and catalytic activity - Gnanakumar, Edwin S.; Thushara, K. S.; Bhange, Deu S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Dalton Transactions, 2011)
Benzyl alcohol has been used to prepare a single phase MgCl2 center dot 6BzOH molecular adduct as a support for an ethylene polymerization catalyst (Ziegler catalyst). The structural, spectroscopic and morphological aspects of the MgCl2 center dot 6BzOH molecular adduct and the Ziegler catalyst have been thoroughly studied by various physicochemical characterization techniques. The presence of MgO6 octahedrons due to the interaction of Mg2+ with six -OH groups of the benzyl alcohol is confirmed from a Raman feature at 703 cm(-1), and structural studies. The supported catalyst activity has been evaluated for the ethylene polymerization reaction. The lower polymerization activity of the titanated Ziegler-Natta catalyst compared with a standard catalyst is attributed to the strong interaction of titanium chloride with the support and associated electronic factors.

MgCl2 center dot 4((CH3)(2)CHCH2OH): a new molecular adduct for the preparation of TiClx/MgCl2 catalyst for olefin polymerization - Thushara, K. S.; Gnanakumar, Edwin S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Dalton Transactions, 2012)
A new molecular adduct of MgCl2 with isobutanol, namely MgCl2 center dot 4((CH3)(2)CHCH2OH) (MgiBOH), has been prepared as a precursor to the supporting material for an olefin polymerization catalyst. The MgiBOH adduct and final titanated Ziegler-Natta catalysts have been thoroughly characterized by powder XRD, thermal analysis, Raman spectroscopy and solid-state NMR for structural and spectroscopy aspects. A peak observed at 712 cm(-1) in the Raman spectra of MgiBOH indicates the characteristic Mg-O-6 breathing mode and the formation of the adduct. The diffraction feature at 2 theta = 7.8 degrees (d = 11.223 angstrom) in the XRD confirms the adduct formation and the layered structure. The aim of the present article is to study how the insertion of a bulky isobutanol moiety affects the structural and electronic properties of the MgCl2 isobutanol molecular adduct. Indeed, the focus of the present study is to explore how the presence of isobutanol, in the initial molecular adduct, influences the final Z-N catalyst properties and its activity.